Information Communication Technologies and Intimate Partner Violence in China - Xue, Jia (International journal of offender therapy and comparative criminology, 2018)
Although a substantial number of studies have investigated factors that influenced intimate partner violence (IPV), very few have assessed the connection between the use of information and communication technology (ICT) and such violence. Using survey data collected from over 400 women in a large Chinese city, this study explored how the involvement of various ICT-related activities affects Chinese women's experiences with psychological, physical, and sexual abuse. We found that some forms of media usage and online activities, such as times spent on paper books and Internet and browsing entertainment and sports news as well as watching movies and TVs online, were linked to a higher or lower likelihood of being a victim of IPV. Feelings of loneliness and helplessness were associated with more IPV victimization experiences. Married women were less likely to experience IPV, whereas working women were subject to greater IPV.